Tworzenie wiedzy technicznej w firmach międzynarodowych - przypadek inwestorów zagranicznych w Polsce - Klincewicz, Krzysztof (Technical knowledge creation by international corporations - the case of foreign investors in Poland, 2006)
The author discusses the creation of technical knowledge by multinational corporations, using the case of foreign investors in Poland. Technical knowledge, related to technology and engineering, is important for the growth and transformation of economies and measured by technical publications and patents. Using bibliometrics, the author analyses 243 largest investors: their involvement in creating technical knowledge and internationalisation of these processes. Polish employees of only 3 companies authored international articles and there were no patents invented. Less than a half of the investors develop technical knowledge, and a limited number carry out truly internationalized R&D operations. The findings suggest that existing investments (focused on access to market and resources) are unlikely to be extended into research-intensive operations, and the development of a knowledgebased economy calls for new sources of knowledge and technologies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1130, s. 233-241